(untitled) (Mustansiria Dental Journal, 2022)
Background: Due to increased chewing capability, one of the most common problems with dentures is that prosthetic teeth can come loose from the denture. The mechanical design of the connection between thermoplastic base materials and acrylic teeth has increased the problem of tooth debonding. Objective: The current study was conducted to assess the shear bind strength of artificial teeth to thermoplastic resin utilizing fusing liquid and mechanical modifications (Alumin-ablasting, T. hole) of tooth ridge lap before and after 100 hours of accelerated ageing. Materials and method: A total 120 maxillary central incisors have been chosen and grouped into 6 groups of 20 samples each, according to surface treatments. each group subdivided into before and after 100hrs according to artificial ageing (n=10). Shear bond strength test conducted by a universal measurement apparatus with crosshead speed 0.5mm / min. Data were statistically analyzed by one-way ANOVA and Tukey’s (HSD). Results: Various surface treatments techniques significantly affected the shear bond strength with statistical high difference in mean bond strength after various surface treatments compared to the control group at (p < 0.001). Regarding surface treatment, Dual treatment of “alumina-blasting + fusion liquid” showed considerably elevated strength compared to alumina-blasting alone at (p < 0.001). also “T. hole +fusion liquid” treatment yielded a significant elevation in strength reading compared to T. hole alone at (p < 0.001). Great significant full in strength value was noted in all groups post 100hrs of artificial ageing process at (p < 0.001). The combined surface treatment revealed the lowest percentage reduction in SBS yielded in (T. Hole + fusion), (Alumina-blasting + fusion) than T. hole alone and alumina-blasting alone after 100hrs of artificial ageing process. Conclusion: Surface treatment with T. hole + fusion liquid or alumina-blasting + fusion liquid enhanced SBS.